2003 Handbook of Employment Regulations Affecting Florida Farm Employers and Workers: Field Sanitation and Drinking Water [State] - Leo C. Polopolus; Michael T. Olexa; Fritz Roka; Carol Fountain (EDIS)
Field sanitation and drinking water regulations provide state standards of field sanitation and drinking water for hand laborers. This is EDIS document FE399, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published July 2003. This information is included in Circular 1200, Handbook of Employment Regulations Affecting Florida Farm Employers and Workers.